2014
DOI: 10.1016/j.mayocp.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death From the Perspective of Coronary Artery Disease

Abstract: Sudden cardiac death accounts for approximately 50% of all deaths attributed to cardiovascular disease in the United States. It is most commonly associated with coronary artery disease and can be its initial manifestation or may occur in the period after an acute myocardial infarction. Decreasing the rate of sudden cardiac death requires the identification and treatment of at-risk patients through evidence-based pharmacotherapy and interventional strategies aimed at primary and secondary prevention. For this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 104 publications
0
35
0
1
Order By: Relevance
“…Our study identified three main characteristics significantly associated with the decision to proceed with coronary angiography within six hours of presentation after OHCA: presentation with ST‐elevation on ECG, an initial shockable rhythm, and a history of coronary artery disease. Initial shockable rhythm and history of CAD are suggestive of a higher pre‐test probability of having an underlying acute coronary syndrome leading to cardiac arrest , and predicted a higher rate of UCA in our study. Prior studies have suggested that male gender, transfer from an outside hospital, presentation with ST‐elevation, and new left bundle branch block were associated with UCA whereas presence of an initial non‐shockable rhythm (pulseless electrical activity or asystole) and low GCS scores were inversely associated with UCA .…”
Section: Discussionmentioning
confidence: 50%
“…Our study identified three main characteristics significantly associated with the decision to proceed with coronary angiography within six hours of presentation after OHCA: presentation with ST‐elevation on ECG, an initial shockable rhythm, and a history of coronary artery disease. Initial shockable rhythm and history of CAD are suggestive of a higher pre‐test probability of having an underlying acute coronary syndrome leading to cardiac arrest , and predicted a higher rate of UCA in our study. Prior studies have suggested that male gender, transfer from an outside hospital, presentation with ST‐elevation, and new left bundle branch block were associated with UCA whereas presence of an initial non‐shockable rhythm (pulseless electrical activity or asystole) and low GCS scores were inversely associated with UCA .…”
Section: Discussionmentioning
confidence: 50%
“…Cardiovascular diseases in Iran, like many other countries, are the leading causes of death and the lost years of life (5). In addition, among the cardiovascular diseases, coronary artery diseases are introduced as the first and the most common cause of death (6).…”
Section: Introductionmentioning
confidence: 99%
“…CAD is the most common cause of SCD in adults >40 years of age, with atherosclerotic CAD accounting for 75% to 80% of the cases in this cohort (19). It also needs to be emphasized that most of these SCD cases involve seemingly normal adults with no symptoms or history of CAD; therefore, some caution should be exercised for explaining the mechanisms of SCD in patients with CAD (20).…”
Section: Cad and Cardiomyopathiesmentioning
confidence: 93%